2022
DOI: 10.31989/ffhd.v12i4.907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inoculation of Lactobacillus acidophilus on the level of nitrite and nitrate in yogurt containing spinach during refrigeration in 21 days

Abstract: Introduction: Yogurt is mixed with spinach in some countries. Spinach can be a probable dietary source of Nitrate and Nitrite, and further N-nitrosamine. Methods: The present study aimed to investigate the effect of inoculation of Lactobacillus acidophilus on the level of nitrite and nitrate in “yogurt containing spinach” (YS) during refrigeration in for 21 days. 4 types of yogurts including yogurt (Y), probiotic yogurt (PY), YS, and probiotic YS (PYS) were produced and kept at 4 °C for 21 days. Their nitrite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…coli.) [2][3][4]. Various studies have demonstrated Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%
“…coli.) [2][3][4]. Various studies have demonstrated Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that experimental mastitis induced either by intramammary infusion of E. coli or Staphylococcal endotoxin results in oxidative stress in dairy cows [28][29][30][31]. Animal modeling of mastitis in rat/mouse has been found to be an appropriate simulation of disease and henceforth allows an in-depth understanding of the pathogenic hotspots [32][33][34][35]. The added advantage of using a rat model includes easy handling, effective mimicking of human/animal diseases, conventionally ease handling of organs, and economic viability [34,35].…”
Section: Introductionmentioning
confidence: 99%